Rancang Bangun Sistem Keamanan dan Pemantau Tamu pada Pintu Rumah Pintar Berbasis Raspberry Pi dan Chat Bot Telegram - Muslimin, Zaenab; Wicaksono, Muhammad Arief; Fadlurachman, Muhammad Fandly; Ramli, Ilham (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Security Systems and Guest Monitoring Prototypes on smart doors Based on Raspberry Pi and Telegram Chat Bot. Current technology is developing so rapidly that it can be used to help people carry out daily tasks at home by designing devices that can be controlled remotely (remote control) so as to create a dream home with increased comfort and safety of residents. This study aims to design a tool for monitoring guests equipped with a security system using the Raspberry Pi microprocessor to process data to be sent to Telegram Chat Bot. Data sent to the Chat Bot Telegram will later be accessed by a smartphone in the form of a guest image taken by a raspberry pi camera. This tool has two modes namely the smart mode that is used to take pictures of guests when a guest presses the bell button and the safe mode is used to take pictures of people who are at the door automatically using a PIR sensor. The results showed that the PIR sensor with maximum sensitivity can detect objects well within a maximum distance of 5 m, the Raspberry Pi camera can take pictures with good quality up to 11m distance and testing on the Chat Bot runs well, all commands have been tested and provide information in the form reciprocal chatter. This prototype allows homeowners to see guests or people at the door through a smartphone in real time.